Time-resolved photoemission at the Si(100)-Ga surface using a femtosecond higher-harmonic laser source - Melzer, Andrea Christine; Kampa, Daniel; Wang, Jinxiong; Fauster, Thomas (Physical Review B, 2009)
The Si(100)-(2x2)-Ga surface was used to investigate time-dependent Ga(3d) core-level shifts by pumping electrons from the valence to the conduction band. The pump-probe experiments were done by exciting carriers with 1.59 eV laser pulses and probing the Ga (3d) core level with higher harmonics. The higher harmonics were generated by focusing laser pulses with 1.4 mJ energy, 30 fs pulse duration, and 779 nm wavelength from a multipass amplifier at a repetition rate of 1 kHz into argon. For the 23rd harmonic, the time resolution of the experiment was similar to 400 fs after a grating monochromator. The band bending of about 110 meV of the p-doped Si(100)-(2x2)-Ga surface is completely lifted by illumination of the surface with the 1.59 eV laser pulses. The Ga(3d) core level shows a slow time-dependent shift attributed to the rise (similar to 1 ns) and decay (similar to 100 ns) of the photovoltage. The Ga(3d) core-level shift and broadening in the femtosecond range are determined to be < 15 meV at the used pump-pulse intensity of 19 mJ/cm(2). Experiments with pump pulses of 3.18 eV photon energy showed similar results.